Prinsip Kmanusiaan Dalam Komunikasi Islam : Kajian Surat Al-Qashash Ayat 1–5 Tentang Sifat Komunikator - Syukri Syamaun (Sadida Islamic Communications and Media Studies, 2024)
This study discusses the principles of humanity in Islamic communication. The focus of his study is on verses 1 to 6 of al-qashash to get a conception of the nature of communicators who listen to God's revelations to increase knowledge of an object. The data in this study were obtained from literature studies through books or journals related to the topics discussed. The results of the study show that the principles contained in the verses of al qashash make Islamic communicators stronger because they listen to a powerful source, namely the Qur'an.